Thyroid peroxidase identified in human granulosa cells: another piece to the thyroid-ovary puzzle?. (3rd July 2017) - Monteleone, Patrizia; Faviana, Pinuccia; Artini, Paolo Giovanni
Abstract: Thyroid hormones seemingly influence the maturation of the human oocyte. Thyroid hormone receptors have been isolated in granulosa mural and cumulus cells and the mature oocyte of the human ovarian follicle. Thyroid hormones are present in follicular fluid in concentrations similar to those in serum. Most importantly, enzymes involved in the chain that regulate the generation of thyroid hormones have been found in granulosa cells. For the first time, we have isolated thyroid peroxidase by immunocytochemistry in the granulosa cumulus cells of the human ovarian follicle, thereby supporting the hypothesis that the human ovarian follicle may be an independent thyroid-hormone producing unit.